Kebangkitan semula Islam di Malaysia: Peranan dan sumbangan Angkatan Belia Islam Malaysia, 1971-2008 / Norazlan Hadi Yaacob - Norazlan, Hadi Yaacob (2017)
This thesis examines the Islamic Resurgence in Malaysia: The Role and Contribution of Muslim Youth Movement of Malaysia (ABIM) from 1971 until 2008. The revival of Islam in Malaysia has a major impact on the changes and the practice of Islam among the Muslim community in Malaysia. The revival process spawned a deep sense of appreciation and religious practice. In order to understand the process of Islamic resurgence in Malaysia, the role and contribution made by ABIM cannot be ignored. ABIM has played as role as an Islamic youth organization that can be characterized as a pressure group in carrying out various demands and programs which have significant impact on society. This study covers the years between 1971 to 2008. Islamic resurgence in Malaysia was seen as the impact of the global Islamic resurgence which took place throughout the world in 1970s. Qualitative method is used in conducting this study whereby library research has been chosen as the key mechanism to select and sort out primary and secondary sources as well as reinforcing them with in-depth interviews with relevant informants. The focus of the analysis is on the role and contribution played by ABIM in creating awareness of Islam to Muslim students in the long run would produce young Muslims who are committed to their religion. In addition, the focus will also be made on the role and contribution of ABIM in the spreading of the idea of Islamization or the setting up of certain institutions as well as establishing good relationships with non-Muslims and the international community. The results of the study exhibit that the birth ABIM in 1971 is a pivotal point in the process of Islamic resurgence in Malaysia. This can be seen from the success of ABIM in spearheading the process of change that led to the birth of a generation of Muslims who are committed to Islam, especially in higher education institutions. These changes which were also supported by the knowledge related activities carried out by ABIM such as establishing usrah groups, publishing and translating of important Islamic books and organizing seminars on Islam. As an Islamic youth organization based, ABIM has also succeeded in carrying out its functions to unify people by taking the initiative to give their views on non-partisan ideas and creating the thoughts on Manhaj Maliziy because Malaysia is a multiracial society that is different from most other countries. Thus, the success of this approach has led to the smooth propagation of Islamic ideas in the society.